The performance and safety of motorized spiral enteroscopy, including in patients with surgically altered gastrointestinal anatomy: a multicenter prospective study - Al-Toma, Abdulbaqi; Beaumont, Hanneke; Koornstra, Jan Jacob; van Boeckel, Petra; Hergelink, Dorien Oude; van der Kraan, Jolein; Inderson, Akin; de Ridder, Rogier; Jacobs, Maarten (Endoscopy, 2022)
Background Data are scarce on the efficacy and safety of motorized spiral enteroscopy (MSE). No data are available on the utility of this technique in patients with surgically altered gastrointestinal (GI) anatomy. We aimed to evaluate the safety and efficacy of MSE in patients with suspected small-bowel disease, including those with surgically altered GI anatomy.Methods A multicenter prospective observational, uncontrolled study evaluated MSE in consecutive patients with suspected small-bowel pathology and an indication for diagnostic and/or therapeutic intervention.Results A total of 170 patients (102 men; median age 64 years, range 18–89) were included. The overall diagnostic yield was 64.1 %. Endotherapy was performed in 53.5 % of procedures. The median total procedure times for the antegrade and retrograde approaches were 45 minutes (interquartile range [IQR] 30–80) and 40 minutes (IQR 30–70), respectively. When total (pan)enteroscopy was intended, this was achieved at rate of 70.3 % (28.1 % by antegrade approach and 42.2 % by a bidirectional approach). Surgically altered GI anatomy was present in 34 /170 of all procedures (20.0 %) and in 11 /45 of the successful total enteroscopy procedures (24.4 %). Propofol sedation or general anesthesia were used in 92.9 % and 7.1 % of the procedures, respectively. Minor adverse events were observed in 15.9 % of patients, but there were no major adverse events.Conclusion MSE seems to be an effective and safe endoscopic procedure. Total (pan)enteroscopy can be achieved, in one or two sessions, even in the presence of surgically altered GI anatomy. The total procedure time is relatively short. For both antegrade and retrograde MSE procedures, propofol sedation seems sufficient and safe.